Concentration and accumulation of nutrients in the aerial biomass of teak plantations 3 to 18 old, in the Panama Canal watershed. - Murillo, Rafael (2015)
Tissue samples from aerial biomass compartments (bark, wood, primary and secondary branches, and foliage) were taken from 16 dominant trees of teak in plantations of the Panama Canal watershed, whose volume yield ranged between 9.4 and 13.3 m3 ha-1. year-1 at ages 3 and 18 years, respectively, growing in clayey, red, and acid Ultisols. Wet and dry weight of the different tissues was measured and subsamples taken to be analyzed for macronutrients (N, K, Ca, Mg, P and S) and micronutrients (Fe, Mn, Zn, Cu and B). Regression analyses allowed to relate nutrients accumulation with tree age. Dry biomass of the wood was 59.6% (C.V. 5%) of total dry biomass, while primary branches, bark, foliage, and secondary branches represented 16.6, 9.4, 7.9, and 6.5, respectively. Larger concentrations of macronutrients were Ca (2.01%) found in the bark, and N in the foliage (1.98%). As for micronutrients, larger concentrations were found in the bark, in the order of Fe (767 mg.kg-1), Mn (60 mg.kg-1) and Zn (50 mg.kg-1). At 18 years of age accumulation of macronutrients was 15.9 kg. tree-1 (7.3 kg Ca, 3.9 kg N, 2.6 kg K, 1.0 kg Mg, 0.7 kg P and 0.4 kg S) and 124 g of micronutrients (89 g Fe, 18 g Zn, 9 g B, 5 g Mn and 3 g Cu).